Sounds good on paper : how to bring business language to life - Horberry, Roger (London : A. & C. Black, 2010)
Figures of speech are pure gold for business writers. They make our words more powerful, persuasive and poetic, and help us get our message across in a way that's immediate and memorable. This book explains 50 of our finest figures and enables people to express themselves with style and impact.
Includes bibliographical references (p. [166]-167) and index.
Keywords: Figures of speech; Business writing